Companies profitability under economic instability: Evidence from the manufacturing industry in Russia - Vladislav Spitsin; Marina Ryzhkova; Darko Vukovic; Sergey Anokhin (Journal of Economic Structures, 2020)
This study analyzes factors affecting the efficiency (profitability) of enterprises in foreign, joint and domestic ownership in countries with unstable economy. The novelty of the study is that for the first time this kind of analysis has been carried out for the manufacturing industry in Russia, whose economy is characterized by the instability (crisis), external sanctions, and the internal trend for import substitution. Using a panel data on 6134 enterprises operating across several industries in Russia over the period of 2012-2016, the article suggests that generally production efficiency and scale efficiency positively affect profitability, whereas the share of borrowed capital, share of fixed assets and rising interest rates exert negative effects. The contribution of external financial factors is minimal, except for foreign and jointly owned firms. Production efficiency has a particularly pronounced effect for the automotive industry, machinery and equipment manufacturing, and in the metal industry. In contrast, in the chemical, electrical and optical manufacturing, and in food processing industries, internal financial factors emerge as a powerful predictor of performance. Firm ownership does not exert a significant effect on the relationship between the variables of interest when the share of borrowed funds is below 50%. When the share of borrowed capital exceeds 50%, internal financial factors emerge as a particularly prominent predictor of profitability.
Keywords: 330; Profitability; Enterprises in Russia; Foreign and joint ownership; Production efficiency; Countries with unstable economies